Mortalidad por desnutrición en Colombia durante la pandemia Covid19 (2024)
Background and objectives: Malnutrition caused by low economic income is a social problem that involves malnutrition as a direct factor in increasing morbidity and mortality. Although malnutrition is considered a low prevalence event in Colombia, its impact is significant. Method: In this study, an ecological analysis was carried out using DANE data on mortality due to malnutrition in Colombia in 2020. Mortality rates per 100,000 people were calculated and compared according to sex and origin (departments). Findings: The results indicated that 1,756 people died from malnutrition in 2020, with a national mortality rate of 3.49 per 100,000 inhabitants. No significant variation in the rate was found. There were no significant differences in the rate according to sex. In Guainía, the mortality rate due to malnutrition was the highest, with 11.0 deaths per 100,000 inhabitants, while, in San Andrés, the rate was the lowest, with 1.57 deaths per 100,000 inhabitants. La Guajira registered the highest mortality rate due to malnutrition in the Caribbean region. Also, compared to the population of the Colombian capital, Bogotá, the population of the Colombian Caribbean presented a 4.62 times greater risk of death due to malnutrition. Conclusion: The findings highlight the importance of addressing the problem of malnutrition in Colombia, particularly in areas with high mortality rates. From an economic point of view, malnutrition has a significant impact on society. The premature death of people suffering from malnutrition means a loss of human and productive capital for the country. Furthermore, malnutrition can lead to disabilities and chronic diseases, which also have a negative impact on the economy.